Impacto de la inteligencia artificial en los entornos de aprendizaje adaptativos para la estimulación cognitiva y emocional de los alumnos del subnivel de educación básica elemental, de la Escuela Jesús de Nazaret, de la ciudad de Guaranda, provincia de Bolívar, período lectivo 2024-2025. - Licuy Andi, Yuly Gabriela (2025)
This research, titled Impact of Artificial Intelligence on Adaptive Learning Environments for the Cognitive and Emotional Stimulation of Students in the Basic Elementary Education Sublevel, addresses the use of technological tools with artificial intelligence to strengthen students' cognitive and emotional stimulation. Its general objective is to evaluate the impact of artificial intelligence in adaptive learning environments, implemented in the educational context of the Jesús de Nazaret School in Guaranda, Bolívar Province. The methodology used was mixed, combining Likert-scale surveys administered to 16 students to analyze aspects such as attention, distraction, frustration, boredom, loneliness, and sadness, along with interviews with teachers and experts to identify the main limitations of current learning environments. The results show that students face recurring attention difficulties and negative emotions such as sadness, boredom, and frustration. In addition, teachers report challenges in addressing the diversity of learning styles, paces, and needs. As a conclusion, the implementation of the Khan Academy Kids application, based on artificial intelligence, is proposed. This tool personalizes the educational experience according to each student's pace and level. Its effective curricular integration, teacher training, and family involvement are suggested as key strategies to improve educational quality in vulnerable contexts.